Burhani Epistemological Order as a Scientific Construction of Islamic Education - Pranajaya, Syatria Adymas; Yunus, Firdaus M; Ikhwan, Muhammad; Syarifaturrahmatullah; Alfiyanto, Afif (International Journal of Education, Language, and Social Science, 2023)
In the realm of Islamic science, al-Jabiri's significant perspective on epistemology, outlined in "an-nidham al-ma'rifi," encompasses Bayani, Irfani, and Burhani dimensions. According to al-Jabiri, Burhani is seen as a solution to revitalize the progress of Islamic world civilization, and it is closely tied to the systematic development of Islamic education. This research, using a literature-based approach, aims to examine how the Burhani epistemological framework contributes to shaping Islamic education. Then, the conclusion can be drawn that the Burhani epistemological order can construct the science of Islamic education as an essential instrument in improving the quality of Islamic education with the process of developing critical and logical thinking skills, can understand the relationship between science and religion, and develop an attitude of tolerance and respect for differences of opinion with the use of rational and logical reasoning. To realize these outcomes, educators must possess a deep understanding of and teaching skills aligned with Burhani epistemology, as well as the design of a dynamic, adaptive, and relevant Islamic education curriculum for the needs of society from generation to generation.